Methodologies for site characterization in crop-animal systems research with an ecoregional approach - Pezo, Danilo A. (International Livestock Research Institute, 1999)
The paper describes a benchmark site, outlines how benchmark sites can serve, lists the purposes of site characterizaiton and examines end-products of site description/characterization. The information required for bio-physical characterization of benchmark sites is presented in a tabular form. The type/source of information includes soil; vegetation and land use; water volume; quality and use; climate; systems in-flows; component interactions; infrastructure; demography/social and economical with the respective variables and frequency are also shown. General stages in the agricultural research process, and levels in the agricultural systems hierarchy are also illustrated.